INVENTARISASI JENIS PAKAN LUTUNG JAWA (Trachypithecus auratus) PADA BLOK CILAME DAN BLOK CIMEUDEUM TAMAN WISATA ALAM GUNUNG TAMPOMAS KABUPATEN SUMEDANG - Raizal Fahmi Solihat; Vina Silvia Bintarawati (Wanamukti: Jurnal Penelitian Kehutanan, 2018)
Javan Langur (Trachypithecus auratus) is one of folivora species by 50 % leaves, 32% fruits, 13% flowers and 7% insects. The most exist of J. langur in Mt. Tampomas Natural Tourism Park in Block of Cilame and Cimeundeum. Mt. Tampomas Natural Tourism Park is one of hiking trails that cause annoyed vegetation as J. Langur’s feed. The objects of studies are to identify of Javan langur’s feed and Importance Value Index of J. Langur’s feed. The method is purposive sampling to know vegetation of feed. The result of species number were 62 species, include 18 species is a J. Langur’s feed. The J. Langur’s feed are kondang (Ficus variegata), nangsi (Villebrunea rubessen), kadoya (Dysoxylum gaudichaudianum), kiara (Fics altisima), kitambaga (Eugenia cuprea), gadog (Bischofia javanica), hamirung (Vernonia arborea), kibanen (Cryteronia paniculata), huru (Machilus rimota), afrika (Maesopsis eminii), putat (Bringtonia acutangular), sampang (Evodia latifolia), pisitan monyet (Glianthus populacus), kilalayu (Lepisanthes tetraphylla), kihuni (Antidesma bunius), hantap (Sterculia coccinea) dan saninten (Castanopsis argentea). Dominance of Javan Langur feed is kadoya (Dysoxylum gaudichaudianum), kitambaga (Eugenia cuprea), dan huru (Machilus rimota). This mean of habitat condition is available feed to J. langur existing.